Molecular Cloning, Functional Characterization And Development Expression Of A New Elongase With Potential Role Of Long-Chain Polyunsaturated Fatty Acid Biosynthesis In A Teleost (Danio Rerio) - Goh, Pei Tian (2020)
Elongase of very long-chained fatty acid (ELOVL) is very important in synthesising long-chained polyunsaturated fatty acid (LC-PUFA). At present, seven members of ELOVL family (ELOVL 1 – ELOVL 7) have been found in mammals. Recently, a putative new Elovl was found in teleost. In order to study and examine the function of this new Elovl, zebrafish (Danio rerio) was chosen. Zebrafish is a viable lipid metabolism model with a complete LC-PUFA biosynthesis pathway and also a very good biological development model. An interest has arisen to determine the elongation capacity and also expression of this elongase of interest during development and in adult tissues. The full length of elongase of interest A (NM_001076593.1) and elongase of interest B (BC095712.1) genes were successfully cloned from the sequence available in National Center for Biotechnology Information (NCBI). A phylogenetic tree was constructed and revealed elongases of interest were grouped as a distinct group from the others elongases (Elovl1-7). Therefore they were named as elovl8a and elovl8b based on the result obtained from the phylogenetic tree. Other than that, Elovl2, Elovl4, Elovl5 and Elovl8 were found originated from the same ancestor and Elovl2, Elovl4 and Elov5 could be the result of gene expansion from Elovl8. Functional characterization of both elongases showed zebrafish Elovl8b converted monounsaturated fatty acid (MUFA), together with C18 and C20 polyunsaturated fatty acid (PUFA) substrates while Elovl8a lacked in these activities.